Does money matter in the Euro Area? Evidence from a new Divisia index - Zsolt Darvas (Bruegel, 2014)
Standard simple-sum monetary aggregates, like M3, sum up monetary assets that are imperfect substitutes and provide different transaction and investment services. Divisia monetary aggregates, originated from Barnett (1980), are derived from economic aggregation and index number theory and aim to aggregate the money components by considering their transaction service. No Divisia monetary aggregates are published for the euro area, in contrast to the United Kingdom and United States. We derive and make available a dataset on euro-area Divisia money aggregates for January 2001 - September 2014 using monthly data. We plan to update the dataset in the future. Using structural vector-autoregressions (SVAR), we find that Divisia aggregates have a significant impact on output about 1.5 years after a shock and tend also to have an impact on prices and interest rates. The latter result suggests that the European Central Bank reacted to developments in monetary aggregates. Divisia aggregates reacted negatively to unexpected increases in the interest rates. None of these results are significant when we use simple-sum measures of money. Our findings complement the evidence from US data that Divisia monetary aggregates are useful in assessing the impacts of monetary policy and that they work better in SVAR models than simple-sum measures of money.
Keywords: 330